Sparger design as key parameter to define shear conditions in pneumatic bioreactors - Esperanca, Mateus N.; Mendes, Caroline E.; Rodriguez, Guilherme Y.; Cerri, Marcel O. [UNESP]; Bettega, Rodrigo; Badino, Alberto C. (Elsevier B.V., 2020)
The average shear rate (<(gamma)over dot>(av)) is a parameter used to characterize the shear environment in bioreactors, enabling comparison of the performances of different bioreactor models in terms of microorganism morphology and viability, and consequently bioproduct formation. Based on this approach, pneumatic bioreactors have been classified as low shear devices. However, the shear behavior cannot be generalized over a wide range of operating conditions, suggesting that the maximum shear rate (<(gamma)over dot>(max)) may be more suitable for the purpose of bioreactor performance comparison. Therefore, the aim of this work was to evaluate average and maximum shear rates in pneumatic bioreactors (bubble column and airlift), based on computational fluid dynamics (CFD) simulations. Concentric-duct and split airlift bioreactors exhibited higher <(gamma)over dot>(av) values, compared to the bubble column design, due to the nature of the liquid circulation patterns. The pneumatic bioreactors exhibited a significant (order of magnitude) difference between <(gamma)over dot>(av) (11.0-27.3 s(-1)) and <(gamma)over dot>(max) 4555 to 25,040 s(-1)), reflecting a non-uniform spatial distribution. The <(gamma)over dot>(max) values occurred close to the sparger holes and presented a linear relationship with gas injection velocity, which is dependent on the sparger geometry. In this way, sparger characteristics (number and diameter of sparger holes) defined <(gamma)over dot>(max) values in pneumatic bioreactors, showing that sparger should be properly designed in order to avoid excessive local shear rates.
Keywords: Pneumatic bioreactor; Computational fluid dynamics; Shear rate; Sparger design